Adherence to the planetary health diet index and metabolic syndrome: cross-sectional results from the PERSIAN cohort study - Sara Shojaei; Zahra Dehnavi; Kiyavash Irankhah; Seyedeh Fatemeh Fatemi; Seyyed Reza Sobhani (BMC Public Health, 2024)
Abstract Background/objectives The Planetary Health Diet Index (PHDI) was recently introduced to assess adherence to the EAT-Lance recommendations. In this study, we aimed to evaluate the relationship between PHDI and metabolic syndrome (MS). Subjects/methods We used the data of 6465 participants from the PERSIAN cohort study at Mashhad University of Medical Sciences, Mashhad, Iran. Diet was assessed using a 130-item Food Frequency Questionnaire (FFQ). The PHDI comprises sixteen components and is scored between 0 and 150 points. We first assessed the validity and reliability of the PHDI for this population. We used regression logistic models to assess the relationships between PHDI and MS and its related indicators. Results The average PHDI score was 52.3 ± 9. The Cronbach’s alpha value was 0.53. After controlling for age and sex, the PHDI was positively related to the Diet Quality Index-International (DQI-I) and was negatively related to carbon and water footprints (p < 0.001). PHDI quartile was negatively associated with MS, hypo-HDL cholesterolemia, and abdominal obesity after controlling for confounders (P < 0.05). Conclusion The validity and reliability of the PHDI were found to be satisfactory for the Iranian population we studied. Our results showed that a higher PHDI was potentially related to a reduced likelihood of MS, hypo-HDL cholesterolemia, and abdominal obesity.